PECULARITIES OF MANOSOCONJUGATES BIOSYNTHESIS BY CELLS OF PANCREAS EPITHELIUM AND MESENCHYME GERMS IN HUMAN EMBRYOS OF DIFFERENT TYPES OF IMPLANTATION - Maystruk, N.I. (World of Medicine and Biology, 2013)
Have been studied 122 human embryos in the age from 21 day to 12 weeks of the intrauterus development, which includes stage X - XXIII and beginning of the fetal period by classification of Carnegie institute and 42 embryos of tubal development to 8 weeks of gestation. Mannosocojugates (receptors of lectin of lens culinaris) in pancreas during uterine implantation appear first for embryos in age 43 days (14 mm of length) on apical surface and cytolemma of epithelial cells. To the end of the second month of embryogenesis mannosocojugates saved at one level. During the third month of development (embryos 30-70 mm of length) glycopolymers accumulate. Differentiation of mesenchymal cells in young fibroblasts is accompanied complete reduction of receptors of lens culinaris lectin. During atypical implantation amount of receptors of lens culinaris lectin changes toward diminishing, that testifies to violation of cells receptor apparatus and processes of adhesion.
Keywords: human early embryogenesis; uterine pregnancy; tubal pregnancy; lectins; organogenesis; pancreas